FUNGSI KOMUNIKASI MASSA DALAM FILM - Muhamad Bisri Mustofa (Program Studi Komunikasi dan Penyiaran Islam, 2022)
Mass communication has a wide area of space in people's lives, with the medium acting as mediator rather than these providing the various roles and functions of mass communication. Particularly in today's rapidly expanding media era, information is accessible very easily and very quickly. In this study, it focused on mass communication functions in KKN Di Desa Penari movie. Researchers use a kind of qualitative study by doing open library studies and interviews using questionnaires by taking 30 persons as sources by category 11 men, and 19 women. From the data collection, there are a number of mass communication functions in KKN Di Desa Penari movie, which is: entertainment function, education function, information function, and persuasion (affecting).